PENERAPAN METODE PEMBELAJARAN KOOPERATIF DALAM POKOK BAHASAN TARI KREASI - Nur Qamariah; Sofyan Salam; Syakhruni Syakhruni (Universitas Negeri Makassar, 2025)
The objectives of this study are: (1) to understand and describe the planning of cooperative learning method in class IX of SMP PPM Al-Ikhlas Lampoko, Polewaali Mandar district, (2) to identify and describe the implementation of dance creation cooperative learning methods in class IX of SMP PPM Al-Ikhlas Lampoko, Polewali Mandar district, and (3) know and describe the assessment of dance creation cooperative learning methods in class IX of SMP PPM Al-Ikhlas Lampoko, Polewali Mandar district. The aim of this research is to explore and describe the planning, implementation, and assessment enhances the learning process, making it more effective compared to conventional methods. Therefore, it can be concluded that the Jigsaw Cooperaative Learning Approach supports the success of the learning process in achieving the subject of arts and culture education at clas IX PPM Al-Ikhlas Lampoko Junior High School, Polewali Mandar district. Keywords: Application; cooperative learning method; creation dance.